Media is stratgies and technologies in communication process (Herald of Journalism, 2019)
The article examines the impact of new media on the public consciousness, all sorts of shapes and styles of expression, socialization and  anagement, which allow to achieve better results in the impact on the public consciousness, as well as the manipulation of the mass  onsciouslution and links it to the unprecedented the development of media and their pervasive influence on public life. The main ideas of research are the basic principles of normative, active and semantic models of communication. For the first time in the studies of K. Jaspers, M. Buber, M. Bakhtin, K.-O. Apel and J. Habermas, communication has been put in the foundations of society and communication ethics. The moral onsciousness defined as the formation of communicative interaction`s structure. Based on this idea of the world’s philosophers, author of this esearch investigates the technologies of manipulation and propaganda of mind control in mass-media, also author analyzes the social and communicative strategies. Also, the conclusions of this research can be used as a source base for the development of cultural policy`s models ofKazakhstan in the field of mass communication.
Keywords: communication, manipulation, management, promotion.